Espaços urbanos : da concepção à concretização - Pereira, Tiago Borges (2005)
The curriculum revision of 2012, that made the discipline of Visual and Technological Ed¬ucation split into two disciplines, but with a common program, presented itself as an opportunity to carry out interdisciplinary projects. This paper, it’s pro-pose a presentation of a teaching experience which consists in the design of urban space and its struc¬tures being implemented in the form of a scale model